Pilot study on the use of soft release for translocation of rehabilitated eastern box turtles (Terrapene carolina carolina) - Alexander, Jacob E.; Debbie Sykes; Healan, Amanda M.B. (Wildlife Rehabilitation Bulletin, 2023)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Successfully rehabilitated eastern box turtles (EBTs, <em style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Terrapene carolina carolina<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">) originating from destroyed or degraded habitats are prime candidates for translocation. However, physiological and behavioral characteristics of chelonians often lead to acclimation difficulties and limited survival post-release. Soft release is a translocation technique whereby an animal is held in a pen on location and allowed to acclimate to its new habitat area for a predetermined duration prior to release. This pilot study explored the viability of small-scale, soft release penning to aid wildlife rehabilitators in the translocation of rehabilitated EBTs. We hypothesized that soft release penning is a practical strategy to help rehabilitated EBTs maintain health and appropriately sized territory in new environments. We built and deployed two soft release pens that were used to relocate three rehabilitated EBTs with varying success to an urban greenspace in Nashville, Tennessee. Our results suggest that soft release penning provides a unique opportunity to observe health and behavior in a controlled environment during the initial period of acclimation, and this early intervention period may help rehabilitators facilitate successful translocation. Further research is recommended to evaluate the direct impacts of soft release pens on body condition, dispersal distance, and home range size of translocated EBTs.